The lived experience of parenting a child with sensory sensitivity and picky eating - Louise Cunliffe; Helen Coulthard; Iain R. Williamson (Wiley, 2022)
Abstract "Picky eating" is a common behaviour seen in childhood in both clinical and nonclinical populations. Sensory processing difficulties have been repeatedly associated with food refusal and picky eating behaviours. The aim of this study was to explore the lived experiences of parents/caregivers who have a child displaying both sensory processing differences and picky eating behaviours utilising Interpretative Phenomenological Analysis (IPA). Participants were recruited from social media support groups for parents of picky eating children. Pre‐selection criteria utilised an adapted short sensory profile questionnaire to ensure the children displayed probable/definite taste‐smell, audio‐visual and tactile sensory sensitivities. Twelve participants fulfilling the required criteria were interviewed face to face utilising a semi‐structured interview schedule. Interviews were transcribed and analysed following IPA guidelines and three common themes are presented here: Battling for control of the sensory environment, Living with stigma and, disapproval, and Staying positive and moving forward. The findings show the very considerable day‐to‐day challenges of parenting a child with sensory issues with food, including a lack of support and criticism from others. It was apparent that the parents in our study gradually adopted a positive and accepting attitude to their child's eating. This acceptance allowed them to have positive interactions around food with their child such as cooking and playing with food, suggesting that experiential activities serve an important purpose in this population. Further research should examine whether parental interventions based on acceptance of child eating behaviour, and commitment to gradual positive food interactions would be the best strategy to support parents and children.